Communication strategy approaches in a Facebook Live Sinar Harian talk broadcast - Salbi, Syairil Adzrin; Abdullah, Muhammad Alif Redzuan; Husain, Salina; Hussin, Sanimah (Human Resource Management Academic Research Society, 2022)
This study investigates the communication strategies (CS) used by the host and guests in a live talk broadcast on Facebook. The aim of the study is to identify and analysed how the respondents compensate for their insufficient linguistic repertoire and enhance their online discussions via the use of the CS in the live talk broadcast. The data was derived from the Facebook Live Sinar Harian talk broadcast on live video streaming on 14 January 2020. Due to the nature of the qualitative research method applied to this study, document content analysis was used. Thematic analysis revealed guest’s employment of an array of CS when interacting during the talk show which includes nine prominent communication strategies used by the host and invited guests in the program, such as abbreviations, denial, questioning, repetition, referral, interruptions, delay, literal translation, and language exchange.